Chapter Introduction - Elstermann, Annika (Taylor & Francis, 2023)
The highly productive subfield of literary studies analysing digital fiction has so far primarily focussed on what makes these digital phenomena new and thus different from their analogue predecessors. This book takes these valuable approaches as a given and sets out to add another piece to the mosaic by instead foregrounding continuities, historical parallels, and pre-digital literary theory to analyse these seemingly new phenomena in a larger context of cultural production and human expression. This introductory chapter outlines the main aims of the book, provides an overview of the material considered in the analysis, and orients the reader in the overall structure of the following chapters.